Analysis of the Impact of Organizational Structure Flexibility on SchoolStakeholders: A Study on Schools in Sleman Regency, DIY - Samanhudi, Jamel Fasha; Riani, Lilia Pasca (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study aims to analyze the impact of organizationalstructure flexibility on school stakeholders in Sleman Regency, SpecialRegion of Yogyakarta. It investigates how flexible structures affectlearning effectiveness, school administrative efficiency, instructionalinnovation, and stakeholder engagement.Design/Methode/Approach : The research employs a qualitative casestudy approach. Data were collected through in-depth interviews anddirect observation involving school principals, teachers, students,administrative staff, parents, and school committee representatives.Thematic analysis was conducted to interpret the findings.Research Finding : The results show that organizational flexibilitypositively influences the quality of teaching and learning, supportsadministrative efficiency, encourages innovation in instruction, andpromotes active stakeholder participation. However, bureaucraticprocedures remain a significant barrier to the optimal implementationof flexibility.Theoretical contribution/Originality : This study contributes to thediscourse on educational management by highlighting how adaptivestructures can drive school transformation toward becoming moreinnovative, collaborative, and stakeholder-oriented learningorganizations.Practitionel/Policy implication : The study suggests the need foradaptive policies and responsive management systems to overcomebureaucratic rigidity and support sustainable school development.Research limitation : The scope of the study is limited to selected publicschools in Sleman Regency using qualitative methods. Future researchmay include broader areas and mixed-method approaches to enhancegeneralizability.